The Role of Criminal Investigation Unit Investigators of Rokan Hilir Resort in Combating the Crime of Human Trafficking Based on Law No. 21 of 2007 Concerning the Crime of Human Trafficking and Human Rights - Wahyu Rio Pradana; Risdalina Risdalina; Kusno Kusno (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Human Trafficking (TPPO) is a serious crime that threatens human dignity and violates fundamental human rights, such as the right to freedom and protection from exploitation. Rokan Hilir Regency, as a border region with high mobility, is one of the areas prone to TIP. This study aims to analyze the role of investigators from the Criminal Investigation Unit (Satreskrim) of the Rokan Hilir Police in efforts to combat TIP based on Law Number 21 of 2007 concerning the Eradication of TIP and its compliance with human rights principles. The method used is an empirical juridical approach through a review of laws and regulations and analysis of field practices. The results of the study indicate that the role of investigators includes preventive, repressive, and coordinative actions, but there are still obstacles such as limited resources, lack of public understanding, and limited victim protection facilities. Synergy between agencies and improving the quality of human resources are key to effective law enforcement.It was concluded that the role of the Rokan Hilir Police Criminal Investigation Unit has been implemented in accordance with the mandate of Law No. 21 of 2007, but requires capacity building, increased inter-agency coordination, and a more victim-centric approach to increase the effectiveness of combating TPPO.